AHP as Multi-criteria Decision Making Technique, Empirical Study in Cooperative Learning at Gulf University - Alsamaray, Hussain Sinjar (European Scientific Journal, ESJ, 2017)
Employment of the Analytic Hierarchy Process (AHP) to assess the contributions of management student team members is described. The students perform this assessment as well as the subject constrictor. The assessments are correlated with the individual team role-assignments to making a final determine of the contributions of the individual to the team effort. Using this evaluation technique appears to provide candidate student peer input for evaluations. The results demonstrated that the student ranking is more likely influenced by the relative importance of teaming, computering skills and management and by sub-criteria, communication, innovation, determination and cooperation. The study sheds importance insight into an area of multi-criteria decision making and Analytical Hierarchy Process (AHP).